A Review on Psychological and Socio-Economic Impacts of Corona Virus Disease (Covid-19) The Case of Under Developing Countries - Desalegn Wondim Alene (Global Journal of Rare Diseases - Peertechz Publications, 2020)
A history signifies that there were different pandemic diseases across the globe at different times that brings a fundamental consequence in psychological, socio-economic and political situations. Evidences showed that most emergency diseases were geographically restricted while others were/are not that attracts the professionals in developing insight and taking cross cutting decision. COVID-19 is the newly emerged pandemic across the globe at the end of 2019 but still shivering the world. Evidences indicated that many countries in the world invest their time, money, energy and strategy to tackle COVID-19 with heavy hesitation for future market instability, hunger and other silent killer diseases as their current plan do not glance to them.